A comparative analysis of serum lipid profile between normotensive and hypertensive pregnant women - K., Sridhara S. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Background: The pregnancy results in the development of the placenta which is characterized by the hormonal changes in the women body, which results in the alteration of lipid profile, diabetic state of the pregnant mothers and many others. Objective of this study was to compare the of serum lipid profile between normotensive and hypertensive pregnant women. Methods: A hospital based cross sectional study was conducted by the department of OBG, Hassan Institute of Medical Sciences, Hassan from July 2018 to December 2018. A total of 6 months the study was conducted. A total of 50 pregnant mothers who were more than 20 weeks of gestation and suffering from Preeclampsia were include in the study group and 50 Pregnant mothers who were more than 20 weeks of gestation and normotensive were included in the controls. Results: Majority of the study subjects in both the groups were less than 25 years of age. The mean age of mothers in study group was 23.19 years and 24.19 years in the control group. The mean HDL level was more among the normotensive group than the pre eclamptic group and the p value was found to be statistically insignificant. The VLDL, LDL and triglyceride level was more in the pre eclamptic group than the normotensive group and the association was also found to be statistically significant. Conclusions: Hormonal changes in pregnancy results in physiological Hyperlipidemia, in conditions like pre-eclampsia triglyceride are elevated more than the normal rise seen in normal pregnancy. Increased lipid profile with raised TG, VLDL, LDL levels leads to the development of Preeclampsia by increasing the oxidative stress and the endothelial dysfunction.